2011
DOI: 10.1021/la201863x
|View full text |Cite
|
Sign up to set email alerts
|

Janus Cylinders at Liquid–Liquid Interfaces

Abstract: We describe the first study on the self-assembly behavior of Janus cylinders at liquid/liquid interfaces. The Janus cylinders are characterized by a phase separation along the major axis into two hemicylinders of different wettability. The pendant drop technique and microscopic imaging were used to characterize the adsorption behavior and self-assembly of Janus cylinders at perfluorinated oil/dioxane and perfluorinated oil/dimethyl sulfoxide interfaces. According to the evolution of the interfacial tension and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 67 publications
5
132
0
1
Order By: Relevance
“…II, we have presented a short proof that the Young-Laplace Eq. (18) and Young's Law (24) derive from the minimization of the thermodynamic potential (Eq. (1)) of the fluid-fluid system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…II, we have presented a short proof that the Young-Laplace Eq. (18) and Young's Law (24) derive from the minimization of the thermodynamic potential (Eq. (1)) of the fluid-fluid system.…”
Section: Discussionmentioning
confidence: 99%
“…(24). Thus, given the fluid volumes and the configuration of the external solid surfaces, the input parameters that determine the shape of the fluid-fluid interface are cos θ and ℓ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Janus particles have been reported to show unique properties that conventional homogeneous particles do not possess, and have been proposed for use in various applications including as amphiphilic surfactants (16), elementary particles of the display in an electric field (17), and particles for magnetolytic therapy (18). Recently, the pulmonary delivery of hydrophilic and hydrophobic anticancer drugs has been reported (19).…”
Section: Introductionmentioning
confidence: 99%
“…Also, they studied the self-assembly of Janus cylinders at liquid/liquid interfaces. They found that the Janus cylinders can significantly enhance surface activity in comparison to homogeneous cylindrical copolymer particles although such Janus cylinders are slightly amphipathic [54]. Further, the Janus concept also can be extended to A-B-A and A-B-C structures except for the general A-B structure.…”
Section: Janus Rods/cylindersmentioning
confidence: 99%